Efeitos da reposição volêmica com hidroxietilamido a 6% versus ringer com lactato após choque hemorrágico controlado em caprinos - Moreira, Maria Alice Pires (Universidade Federal Rural do Semi-Árido, 2017)
Haemorrhagic shock is an important cause of death and its reversal and treatment can help patients, furthermore it can minimize deleterious effects. Significant loss of the intravascular volume causes haemodynamic instability with decrease of tissue perfusion and cellular hypoxia and the reversal and treatment of shock increase the survival of patients and decreases deleterious effects of acute haemorrhage. Volume expandors can bring benefits and increase the survival of an individual. Synthetic substances can change the prognosis and reverse the clinical outcome in situations where there are neither blood bags nor donor available. Lactated Ringer and Hydroxyethylamide are solutions with biochemical and molecular features advantageous in the first stages of hemorrhagic shock treatment. Despite these features, more studies are necessary to determine their real benefits and deleterious effects. Evaluation of physiological parameters helps intensive care specialists monitoring patients in acute blood loss, and focused assessed transthoracic echocardiography is considered important tool in shock prevention or diagnosis. In this area, research is often carried out on small ruminants once they are considered more suitable for clinical evaluation and elaboration of treatment strategies. Goats can be considered a good experimental model, however data related to cardiovascular evaluation under haemorrhagic shock are still rare in this species. Thus to obtain more information to apply across different species (in veterinary and human medicine), this study aimed to describe anatomic and funcional features of heart and vessels in goats using transthoracic echocardiographic exam and to compare effects of Hydroxyethylamide and Lactated Ringer’s solution during volume replacement following experimental hemorrhagic shock in goats
Volemic replacement with hydroxyethil starch 6% versus lactated ringer after controled hemorrhagic shock in goats
Keywords: Fluidoterapia; Terapia Intensiva; FAST; Pequenos Ruminantes; Anestesia; Fluid therapy; Critical Care; FAST; Small Ruminants; Anesthesia; CIENCIAS AGRARIAS::MEDICINA VETERINARIA